2006
DOI: 10.1111/j.1439-0310.2006.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shape on Egg Discrimination in American Robins and Gray Catbirds

Abstract: The eggs of some obligate brood parasites are more spherical than the eggs of their non‐parasitic relatives and hosts, which contributes to the increased strength of their shells. We examined whether egg shape, including the more spherical shape of brown‐headed cowbird eggs (Molothrus ater), influenced egg discrimination in American robins (Turdus migratorius) and gray catbirds (Dumetella carolinensis). We added a series of artificial objects to robin and catbird nests that varied in shape from a control host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 51 publications
4
58
0
Order By: Relevance
“…In addition, some hosts do not practice nest sanitation, but can reject some eggs (Peer 2017). Underwood and Sealy (2006) suggested that the ability of American Robins and Gray Catbirds (Dumetella carolinensis) to recognize non-egg objects was significantly higher than that of other species without egg discrimination ability. Moskát et al (2003) examined the relationship between nest sanitation and egg rejection in the Great Reed Warbler (Acrocephalus arundinaceus) and showed that the rejection rates of the non-egg models were significantly higher than those of cuckoo model eggs, either during hatching or in the early stage of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some hosts do not practice nest sanitation, but can reject some eggs (Peer 2017). Underwood and Sealy (2006) suggested that the ability of American Robins and Gray Catbirds (Dumetella carolinensis) to recognize non-egg objects was significantly higher than that of other species without egg discrimination ability. Moskát et al (2003) examined the relationship between nest sanitation and egg rejection in the Great Reed Warbler (Acrocephalus arundinaceus) and showed that the rejection rates of the non-egg models were significantly higher than those of cuckoo model eggs, either during hatching or in the early stage of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…However, egg rejection by hosts may be an extension of their nest sanitation behavior (Rothstein 1975;Guigueno and Sealy 2009;Yang et al 2015b). Many studies have shown the relationship between the nest sanitation behavior and egg discrimination ability of cuckoo hosts using various nonovoid foreign objects (Ortega and Cruz 1988;Moskát et al 2003;Underwood and Sealy 2006;Yang et al 2015a, b;Luro and Hauber 2017;Peer 2017;review Moskát et al (2003) proposed that the less similar the shape of a foreign object to a cuckoo egg, the higher the host rejection rate, so that the ability of the host to recognize a cuckoo egg is an extension of its nest sanitation behavior. In addition, hosts with strong egg discrimination ability tend to be more capable of rejecting non-ovoid objects than are hosts without egg discrimination ability (Yang et al 2015b), indicating that host egg discrimination ability is associated with nest sanitation behaviour (Underwood and Sealy 2006;Guigueno and Sealy 2009;Yang et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving experimental addition of objects have given insight into the genetic basis of nest sanitation and its relationship with the rejection responses of some hosts of brood parasites (Smith 1943;Bártol et al 2003;Moskát et al 2003;Underwood and Sealy 2006a). The subject has not been reviewed, despite that the study of nest sanitation has drawn increased interest (Ortega and Cruz 1988;Ortega et al 1993;Bártol et al 2003;Moskát et al 2003;Underwood and Sealy 2006a;Guigueno and Sealy 2009).…”
Section: Introductionmentioning
confidence: 92%
“…The removal of non-egg-shaped objects has been considered a type of nest-sanitation behavior (Alvarez et al 1976;Bártol et al 2003;Moskát et al 2003;Underwood and Sealy 2006a;Guigueno and Sealy 2009). Studies involving experimental addition of objects have given insight into the genetic basis of nest sanitation and its relationship with the rejection responses of some hosts of brood parasites (Smith 1943;Bártol et al 2003;Moskát et al 2003;Underwood and Sealy 2006a).…”
Section: Introductionmentioning
confidence: 97%